Shear strengthening of reinforced concrete T beams with Hybrid Composite Plate (HCP) - Baghi, Hadi (2016)
This paper aims to evaluate the effectiveness of hybrid composite plates (HCPs) technique for the shear strengthening of the reinforced concrete (RC) T cross-section beams. HCP consists of a thin plate of strain hardening cementitious composite (SHCC) reinforced with carbon fiber reinforced polymer (CFRP) laminates. Two HCPs with different CFRP laminates percentage (ρfw=0.08% and ρfw=0.14%) were adopted for the shear strengthening of the beams. The HCPs were bonded to substrate in two different ways. In the first case, the HCPs were bonded using epoxy adhesive, whereas in the second case they were bonded using epoxy adhesive and fixed by mechanical anchors. The effectiveness of this technique was limited by the tensile strength of the concrete cover of the strengthened beams. Therefore, in the second case, mechanical anchors prevented a premature debonding of the HCPs and a certain concrete confinement was applied in the zone of the beam to be strengthened, resulting in favorable effects in terms of shear strengthening. Advanced finite element method (FEM) based numerical simulation was performed by using a constitutive model, whose predictive performance was demonstrated by simulating the experimental tests carried out. After demonstration of the good predictive performance of the numerical model, a parametric study was carried out to study the influence of the shear reinforcement ratio, and the influence of thickness of the HCPs on the beam’s load carrying capacity.